Does the traditional recruitment procedure of higher education institutions cause paper waste? - Mahmood Rehmani; Umer Iftikhar; Munnawar Naz Khokhar; Hafiz Ihsan Ur Rehman; Huda Irshad; Naveed Anwer (Cogent Business & Management, 2022)
Solid waste management has become one of the critical environmental concerns in developing countries. Information and communications technology have revolutionized traditional organizational management processes, increased efficiency, and significantly reduced paper use. The recruitment process in higher education institutes (HEIs) includes job applications and certificates of degree, and previous job-related documents. Such recruitment policies are causing paper waste and need the attention of policymakers. This study aims to provide empirical evidence for a policy shift that can have a broader impact on the environment. The current study aims to contribute to the existing research by considering the traditional recruitment approaches of public sector HEIs in Pakistan as a source of solid waste. The study highlights the previously disregarded aspect of the research on solid waste and explores the traditional practices of government-owned HEIs that lead to excessive amounts of paper waste. A mixed-methods approach is performed to confirm this hypothesis. We observed newspaper advertisements and then floated a questionnaire among employees of the HEIs. Findings confirm that traditional recruitment is one of the primary antecedents of paper waste generation. Results suggest that technology-driven recruitment reduces paper waste and leads to sustainable development.
Keywords: 650; sustainability; information communication technology; recruitment policy; waste management; waste reduction